Effect of the downward bevel angle on the particle radial migration behaviour and secondary flow in spiral separators - Lingguo, Meng; Shuling, Gao; Tianlin, Liu; Jingzhong, Kuang; Mingming, Yu (Minerals engineering, 2025)
•Larger downward bevel angle hinders outward particle migration via weakened flow.•Downward bevel angle shifts particle enrichment zones radially inward.•Inward flow mixing exacerbates misplaced quartz in concentrate stream.•The relationship between secondary flow and particle radial migration is revealed. Parabolic cross-sectional spiral separators are commonly used to separate fine particles, and the downward bevel angle is a key parameter for adjusting the geometry of a parabolic cross-sectional curve. However, the influence of the downward bevel angle on particle separation in a spiral separator remains unclear. In this study, numerical simulation methods were employed to analyse the fluid flow characteristics and particle motion patterns in a spiral separator under different downward bevel angles. The results indicate that a significant radial migration of particles occurred in the first turn and increasing the downward bevel angle can hinder the outward migration of particles by weakening the strength of the outward flow. As the trough length increased, the effect of the downward bevel angle on the radial migration of the particles gradually decreased. After the initial radial separation, the misplaced particles depend on the enrichment ratio of hematite in the outwards flow of the outer trough or the enrichment ratio of quartz in the inward flow of the inner and middle troughs. Misplaced particles cause mixing phenomena, which adversely affect the subsequent separation. In the stable stage, the separation efficiency was closely related to the mixing zone. The separation efficiency was maximised when the downward bevel angle was 6°. Regulating the secondary flow characteristics in the mixing zone and the distribution of particles in the inward and outward flows are the important methods for enhancing the separation performance. The research findings provide a scientific basis for optimising the spiral separator design and improving the separation efficiency.